FROM HARD TO SIMPLE USING «SHYSHAKY TECHNOLOGIES» - Падалка, В. В. (Scientific Progress & Innovations, 2015)
This work is dedicated to the problem of ecological agriculture. The analysis of existent technologies of minimum soil cultivation is conducted. The more similar examples to ecological agriculture are separated on the example of implanted system in PE «Agroecology». We offer a system of concepts of soil cultivation for maintaining its fertility and growing ecologically clean products of crop production. We light up the problem of insufficient maintenance of moisture and ways of destruction of non-arable sole by mechanical and biological character. We offer an example of technological operations of soil cultivation that is implanted for ecological and biologically restorative agriculture.